Federalism in Nepal: Cultural Transformation, Governance Challenges, and Opportunities for Inclusive Development - Aryal, Arjun Dhooj (THE ACADEMIA, 2026)
Federalism in Nepal represents one of the most significant political transformations in the nation’s modern history. Adopted formally with the promulgation of the 2015 Constitution, federalism was envisioned as a mechanism to decentralize power, promote inclusion, and address long-standing inequalities rooted in geography, ethnicity, and governance. This paper critically examines the cultural, political, and economic dimensions of Nepal’s federal experiment. Drawing on theoretical perspectives of federalism and empirical evidence from Nepal’s socio-political context, the study highlights challenges such as duplication of bureaucratic structures, fiscal burdens, weak institutional capacity, and rising provincial sentiments that sometimes undermine national unity. It also explores cultural processes such as Nepalization, Sanskritization, and migration, which have shaped national identity and influenced federal restructuring. Using a qualitative methodology based on secondary literature, constitutional provisions, and audit reports, the paper identifies gaps between federal ideals and practice. Findings suggest that while federalism offers opportunities for grassroots democracy, fiscal autonomy, and social inclusion, it also risks exacerbating ethnic divisions and administrative inefficiencies if not carefully managed. The study concludes that Nepal’s federalism must be tailored to its unique diversity, emphasizing cooperation, fiscal discipline, and cultural integration. Recommendations include strengthening intergovernmental coordination, enhancing administrative capacity, and fostering a shared national identity rooted in pluralism. Ultimately, federalism in Nepal represents both a challenge and an opportunity: its success depends on strategic reforms and the commitment of political actors to unity and inclusive development.